Protracted diarrhea in infants and young children: a clinical evaluation with special reference to the role of infection - Muzief Munir (Paediatrica Indonesiana, 1982)
Since diarrheal disease is one of the IIwst prominent child health problem in Indonesia, a great deal of effort has been made to reduce morbidity and mortality rates of acute diarrhea.Only a very small number of diarrheal cases, 49 oul of 1186 cases (4%) are protracted diarrhea, which can be divided into acute onset of protracted diarrhea without failure to thrive in 16 cases, chronic recurrent diarrhea with failure to thrive in 10, and chronic recurrent diarrhea without failure to thrive in 2 cases.Malaria plays an important role in 10 cases of failure to thrive with protracted diarrhea, and in 3 acute onset of prolonged diarrheal cases without failure to thrive.Amebiasis is found in 3 cases of acute onset of prolonged diarrhea. E. coli is found in 8 cases of acute onset of prolonged diarrhea without failure to thrive, in 2 cases of acute onset of prolonged diarrhea and failure to thrive, in 1 case of prolonged diarrhea in multiple congenital malformation and failure to thrive, and in 1 case of chronic recurrent diarrhea in colostomy and failure to thrive.A massive dose of vitamin A is recommended to be given to all of the protracted diarrhea cases, since 6 out of 49 cases evidenced a marked vitamin A deficiency.